Serum Lipid Profile in Adult Nephrotic Syndrome Patients - Rahman, Taniza; Sultana, Nasima; Molla, Golam Morshed; Mazumder, Pinke; Chowdhury, Sanjeela Nahreen; Rahman, Irin (Delta Medical College Journal, 2018)
Background: The nephrotic syndrome is a constellation of abnormalities that includes massive proteinuria, hypoalbuminaemia and oedema. Lipid abnormalities have an important biochemical basis in the disease process of adult nephrotic syndrome. Dyslipidaemia in nephrotic syndrome is involved in cardiovascular risk and also accelerates the progression of glomerular dysfunction. Objective: To find out the association between serum lipid profile and nephrotic syndrome in adult. Materials and method: This case control study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka, Bangladesh, during the period of July 2013 to June 2014 to evaluate the association of serum lipid profile in adult patients with nephrotic syndrome. One hundred (100) study subjects were included, among them fifty (50) were diagnosed adult nephrotic syndrome patients selected as case and fifty (50) were age and sex matched healthy adult individuals selected as control. Serum lipid profile and serum albumin were measured for both case and control. All the statistical analyses were done by using SPSS for Windows version 20.0. Results: Mean±SD of serum total cholesterol (Tchol), triacylglycerol (TAG), high density lipoprotein (HDL-C), and low density lipoprotein (LDL-C) of case were 288.23±35.67 mg/dL, 174.53±18.86 mg/dL, 23.71±4.58 mg/dL, and 231.16±34.28 mg/dL respectively and that of control were 171.04± 24.36 mg/dL, 129.58± 23.47 mg/dL, 37.5± 7.01 mg/dL, and 103.58±36.83 mg/dL respectively. Serum Tchol, TAG, LDL-C levels were significantly higher in cases than the control (p<0.0001) and serum HDL-C level was significantly lower in cases than the control (p<0.0001). Conclusion: Dyslipidaemia is associated with adult nephrotic syndrome. Routine check-up of lipid profile will help to prevent the development of cardiovascular and cerebrovascular complications in adult nephrotic syndrome patients. Delta Med Col J. Jan 2018 6(2): 78-81